PERENCANAAN PERBEKALAN OBAT DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH TELUK KUANTAN TAHUN 2021 - Alfan Najmi; Restu Prihandini Widiar (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2022)
Background: Planning for drug supplies in hospitals is the process of procuring drug supplies in hospitals with the aim of estimating drug needs based on data on drug use within a certain period of time in the hope that drugs are always available in each hospital service unit. In planning for pharmaceutical supplies, there are still limited drug stocks and excess drug stocks for certain types of drugs at the end of the year. This is due to inaccurate recording of drug use and due to insufficient budget availability. Methods: This type of research is a descriptive study with a qualitative method approach, carried out at Teluk Kuantan Hospital with a total of 4 informants, namely the Head of the Pharmacy Installation, the Planning Sub-Division, and the Pharmacy Installation Officer. This research was conducted by conducting in-depth interviews and observations and data processing was carried out by source triangulation, method triangulation and data triangulation. The data obtained were analyzed with relevant theories. Results: The results showed that the planning of pharmaceutical supplies, drug selection, compilation of drug use, drug calculations and evaluation of drug planning had been carried out according to standard procedures but the technical implementation had not been carried out optimally. Conclusion: The pharmaceutical supply planning process has been running but the results have not been as expected. Some of the underlying constraints are the limited budget allocation so that drug preparations tend to be reduced or alternative generic preparations are sought. In addition, inaccurate recording of drug use makes the calculation of pharmaceutical needs inaccurate. It is hoped that officers will be more careful in recording drugs and looking for solutions to budget needs, so that drug needs from the quality and quantity aspects can be met at the pharmaceutical installation of Teluk Kuantan Hospital.